436 Risk of workaholism among hospital medical staff: an epidemiological study. (24th April 2018) - Pougnet, R; Pougnet, L; Saliou, P; Le Menn, A; Dewitte, JD; Loddé, B; Bodenez, P
Abstract : Introduction: 'Workaholism', an addiction to work, is a pathology which has been recognised since the 1970s. It is generally found in around 10% of workers, yet one study on doctors working in a hospital environment demonstrated that 30% suffered from the condition. This study's objective is to evaluate the prevalence of workaholism among doctors in a university teaching hospital, and to analyse the links to working conditions and the imbalance between effort and reward. Methodology: Cross-sectional survey of doctors in a university teaching hospital, using an anonymous online questionnaire via Sphinx Online© software. The questionnaire consisted of general questions, specific questions on psychoactive substances (tobacco, alcohol, cannabis and others), Siegrist's effort-reward imbalance questionnaire and the Work Addiction Risk Tests (WART) questionnaire. Results were analysed using Excel© and Biostatgv©. Reuslts: There were 162 participants, a rate of 30% of relevant personnel. The principal psychoactive substance used by participants was alcohol: 81.3% of subject reported consuming it. An effort-reward imbalance was present in 18% of subjects who participated in the study. The risk of workaholic was identified in 48% of the cohort: 17% were high risk and 31% medium risk. There was a link between workaholism and effort-reward imbalance (p<0, 001). Conclusion: The frequency of workaholism among doctors is much higher than the general population. From this study the link with work-related stress may help direct primary prevention efforts for this condition.